Use of digital platforms in English Language Teaching - Avilés Menjivar, Rafael Antonio; Muñoz Rivas, Luis Osvaldo; Aparicio Bustillo, Guillermo José (2024)
The Foreign Language Department of the University of El Salvador introduced a specialization course designed for students of the Bachelor’s degree in English with an emphasis in teaching and the Bachelor´s degree in Modern Languages with an emphasis in French and English. They did it to provide the alternatives for undergraduate students to complete their graduation process. The authorities implemented a course to increase the knowledge and abilities of students about online teaching and learning. This report contains details on how the research team carried out activities and created material used during the course. Additionally, it shows the achievements they accomplished during the development of the specialization course and how they put into practice what they learned through online teaching and learning. Finally, the participants provide suggestions to improve teaching and learning quality at the Foreign Language Department of the School of Humanities. Key words: E-learning ; Virtual learning ; Asynchronous and Synchronous Learning ; Online Teaching ; Flipped Learning